Integrating Traditional Decorative Arts into Modern Interior Design Education - Raxmonova E’zoza Zoir qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines methods for incorporating traditional decorative arts into modern interior design education. It highlights how combining national motifs with contemporary design principles enhances students’ aesthetic perception, creative thinking, and practical design skills. The study emphasizes interactive learning, project-based exercises, and digital modeling as tools to help students develop visually appealing, functional, and culturally meaningful interior spaces.